SPP1 expression indicates outcome of immunotherapy plus tyrosine kinase inhibition in advanced renal cell carcinoma - Xianglai Xu; Jinglai Lin; Jiahao Wang; Ying Wang; Yanjun Zhu; Jiajun Wang; Jianming Guo (Human Vaccines & Immunotherapeutics)
Clinical guidelines have recently advised combination therapy involving immunotherapy (IO) and tyrosine kinase inhibitors (TKI) as the first-line therapy approach for advanced renal cell carcinoma (RCC). Nevertheless, there is currently no available biomarker that can effectively distinguish the progression-free survival (PFS). RNA-sequencing and immunohistochemistry were conducted on our cohort of metastatic RCC patients, namely ZS-MRCC, who received combination therapy consisting of IO and TKI. We further applied RNA-sequencing, immunohistochemistry, and flow cytometry to examine the immune cell infiltration and functionality inside the tumor microenvironment of high-risk localized RCC samples. SPP1 expression was significantly higher in non-responders to IO-TKI therapy. Elevated levels of SPP1 were associated with poor PFS in both the ZS-MRCC cohort (HR = 2.73, p = .018) and validated in the JAVELIN Renal 101 cohort (HR = 1.61, p = .004). By multivariate Cox analysis, SPP1 was identified as a significant independent prognosticator. Furthermore, there existed a negative correlation between elevated levels of SPP1 and the presence of GZMB+CD8+ T cells (Spearman’s ρ= −0.48, p < .001). Conversely, SPP1 expression is associated with T cell exhaustion markers. A significant increase in the abundance of Tregs was observed in tumors with high levels of SPP1. Additionally, a machine-learning-based model was constructed to predict the benefit of IO-TKI treatment. High SPP1 is associated with therapeutic resistance and unfavorable PFS in IO-TKI therapy. SPP1 expression have also been observed to be indicative of malfunction and exhaustion in T cells. Increased SPP1 expression has the potential to serve as a potential biomarker for treatment selection of metastatic RCC.